Cytomegalovirus infection and end-organ disease in Asian patients with lymphoma receiving chemotherapy. Issue 1 (January 2014) - Tay, Matthew Rong Jie; Lim, Soon Thye; Tao, Miriam; Quek, Richard Hong-Hui; Tay, Kevin; Tan, Thuan Tong
Abstract This study aimed to describe the epidemiology and risk factors for cytomegalovirus (CMV) infection and end-organ disease in patients with lymphoma undergoing potentially curative or salvage therapy. We retrospectively reviewed 534 patients with lymphoma treated at an Asian tertiary cancer center between January 2007 and December 2010. Overall, 48 patients (9.0%) experienced CMV infection, with 12 patients (25.0%) being further diagnosed with CMV end-organ disease. Many patients with CMV infection were male, with poor performance status, non-Hodgkin lymphoma and advanced disease, and received rituximab use. Moreover, patients receiving rituximab and HyperCVAD (hyperfractionated cyclophosphamide, vincristine, doxorubicin and dexamethasone) regimens had a high rate of CMV end-organ disease. In Asian patients with lymphoma receiving curative or salvage therapy, CMV infection was relatively common (9.0%). Most of these were likely to be reactivation in nature. A small group, especially those on rituximab or HyperCVAD, developed CMV end-organ disease (12/534). Such patients should be monitored closely for CMV end-organ disease. Alternatively, prophylaxis should be studied.